AN EFFECT OF APPLICATION SYSTEM ORGANIC FERTILIZERS AND ECOENZIM ON GROWTH SOYBEAN EDAMAME (Glycine max L. Meril) - Wahyu Pratama; Najla Lubis; Devi Andriani Luta (Sean Institute, 2022)
This study aims to determinethe effectiveness of chicken manure and ecoenzymes on the growth of soybean (Glycine max L. Merril) plants. This study used a factorial randomized block design (RAK) with 2 treatment factors, 16 treatment combinations and 2 blocks so that there were 32 plots. Treatments (1) Chicken Manure Organic Fertilizer (A) consisted of A0 = No Chicken Manure Organic Fertilizer, A1 = Chicken Manure Organic Fertilizer 7.00 g/plot, A2 Chicken Manure Organic Fertilizer 1,400 g/plot, A3 Chicken Manure Organic Fertilizer 2,100 g/ plots. For treatment (2) Ecoenzyme (R) consisted of R0 = Without Ecoenzyme Treatment, R1 = Ecoenzyme Treatment 1:100, R2 = Ecoenzyme Treatment 1: 200, R3 = Ecoenzyme Treatment 1:300. The changes observed were plant height (cm), and number of leaves (strands).